2009
DOI: 10.1021/ie801818n
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Water-in-Oil Emulsion Viscosity in Porous Media

Abstract: Experiments have been conducted to determine the viscosities of water-in-oil (W/O) emulsions in porous media. W/O emulsions were first prepared for different volume fractions of the dispersed phase and then characterized for their properties and rheological parameters including flow index and consistency constant. All prepared W/O emulsions with volume fractions between 6.78% and 33.48% were found to behave as non-Newtonian shear-thinning fluids at fairly high viscosities. The viscosities of the emulsions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 19 publications
6
42
0
Order By: Relevance
“…Emulsion flow through porous media is an important phenomenon in oil production operations and is also a topic of special interest in many applications of science and engineering, especially petroleum industries (Soo and Radke 1984;Soma and Papadopoulos 1995;Vidrine et al 2000;Arhuoma et al 2009;Cobos et al 2009). It has been suggested that oil migrates through reservoir sands in the form of a fine, dispersed emulsion of oil in water, and that oil accumulations occur where the stream enters finer-grained rock such as silt or shale.…”
Section: Introductionmentioning
confidence: 99%
“…Emulsion flow through porous media is an important phenomenon in oil production operations and is also a topic of special interest in many applications of science and engineering, especially petroleum industries (Soo and Radke 1984;Soma and Papadopoulos 1995;Vidrine et al 2000;Arhuoma et al 2009;Cobos et al 2009). It has been suggested that oil migrates through reservoir sands in the form of a fine, dispersed emulsion of oil in water, and that oil accumulations occur where the stream enters finer-grained rock such as silt or shale.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these columns may be split there and gradually transformed into small water droplets-w=o emulsion. All these dispersions exhibit good Jamin effect and high viscosity, [13][14][15] so the fingering effect is greatly suppressed.…”
Section: Alkali As the Displacing Agentmentioning
confidence: 99%
“…4) With the formation of a W/O emulsion, the pressure drop across the micromodel increased. This is because that the water-in-heavy oil emulsion has a much higher viscosity than the water and the resistance to water flow in the water channels are increased significantly 21 . This is the mechanism that will be studied in alkaline flooding for heavy oil to improve sweep efficiency and thus oil recovery.…”
Section: Micromodel Observationsmentioning
confidence: 99%